Animal husbandry practices of Soliga tribe in core and buffer zone of Biligiri Rangana hills of Karnataka - SOMAGOND, ARUN S; PATEL, B H M; GAUR, G K; SINGH, M; DUTT, TRIVENI; VERMA, M R; UMAPATHI, V; THAMOTIRAN, THAMOTIRAN; SANYAL, A (The Indian Journal of Animal Sciences, 2019)
Soliga tribe is one of the most backward tribe among all other tribes in Karnataka and still they are not in mainstream of the society. Majority of the Soligas are rearing livestock species and cattle and goats are predominant ones. This contributes seasonal income. It can be concluded that Soligas in the buffer zone had better access to treatment and marketing facilities than core zone.